PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV TUNA RUNGU DI SLB NEGERI DUMAI - Darta Elina Darta Elina; Hendri Marhadi Hendri Marhadi; Gustimal Witri Gustimal witri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract.This research based on the result of the improvement of IV grade deaf students of SLBN Dumai in Social Science (IPS) subject. From 12 students only 4 students (49.17) passed  the minimum completeness criteria which is 60. The formulated problem in this research whether the application of Direct Instruction can improve students’ grade in Social Science (IPS) subject of IV grade deaf students in SLBN Dumai. The aim of this research is to improve students’ grade in Social Science (IPS) subject with application of Direct Instruction. This research use classroom action research through Direct Instruction at fourth grade deaf students of SLBN Dumai within 12 students. This action was done at April 2014. The initial results, only 4 students or 49.17 achieved minimum completeness criteria (60) and the average value was 49.17. After applying direct instruction in the classroom, at UH I cycle 1, the number of students who passed the minimum completeness criteria increased to 8 students (70.66%) with an average value 70.83. At UH II In the second cycle, the number of students who achieved a minimum completeness criteria also increased to 10 students (83.3%) with an average value was 82.5. Based on these results, it can be concluded that the direct instruction can improve deaf students’ achievement in IPS subject. Direct instruction closely matches the Deaf students who have difficulty in communication. It is suggested that classroom teachers should use direct instruction model for teaching and learning activities of deaf students. Key Words: Direct Instruction, Students’ Achievement in Social Science.